Bone conductive implantation in asymmetric hearing loss (AHL). (31st July 2020) - Monini, Simonetta; Battilocchi, Ludovica; Salerno, Gerardo; Filippi, Chiara; Barbara, Maurizio
Abstract: Background: Bone conductive implants (BCI) represent one possible solution for rehabilitation of single-sided deafness (SSD). Aims: The aim of the present study was to verify the efficacy of bone conduction implantation in subjects with unilateral severe-to-profound hearing loss and contralaterally impaired hearing, that is, asymmetric hearing loss (AHL), and to compare it with known BCI indications for SSD. Material and methods: Twenty-one subjects received BCI for either SSD or AHL. All of the subjects underwent a battery of audiological and subjective tests, Data were collected and statistically evaluated within and between the SSD group and the AHL group. Results: A PTA threshold gain was observed in AHL patients along with improved values in speech audiometry in quiet and noise. The two visual analogue scale evaluations (QoL and QoS) and the GBI showed significantly better scores in AHL patients compared to SSD patients. Conclusions: BCI provided improvement for auditory or speech recognition in AHL subjects, as compare to SSD. From these findings, it is possible to predict a positive role of BCI for some audiological aspects of AHL subjects that are generally not present or not detectable in SSD cases.